This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
For this, we need to use the complex definition of the sine function (derived from Euler's Formula ):
sin ( z ) = 2 i e i z − e − i z
We can set this to be 2 and then we can neaten it up:
2 i e i z − e − i z = 2 ⟹ e i z − e − i z = 4 i
We can now multiply both sides by e i z and we can form a quadratic equation:
e i z − e − i z = 4 i ⟹ ( e i z ) 2 − 1 = 4 i e i z ⟹ ( e i z ) 2 − 4 i e i z − 1 = 0
Now, using the Quadratic Formula , we can determine that, with a = 1 , b = − 4 i , c = − 1 :
e i z = 2 ( 1 ) − ( − 4 i ) ± ( − 4 i ) 2 − 4 ( 1 ) ( − 1 ) ⟹ e i z = 2 4 i ± − 1 2 ⟹ e i z = i ( 2 ± 3 )
Now, we can take the natural log to get:
i z = ln ( i ( 2 ± 3 ) ⟹ i z = ln ( i ) + ln ( 2 ± 3 )
Since we know that ln ( i ) = e i 2 π and we are only taking the principle value we can say that
i z = i 2 π + ln ( 2 ± 3 )
Now we can divide by i to find that
z = 2 π − ln ( 2 ± 3 ) i